Model Pendidikan Multikultural dalam Perspektif Pendidikan Islamdi Sanggar Bimbingan Sungai Mulia 5 Malaysia - Eliyawati; Supratno, Haris (PAI RAFAH, 2024)
Multiculturalism is basically a universal view which can then be translated into various cultural policies that emphasize acceptance of religious, plurality and multicultural realities that exist in community life and the Sanggar Guidance Sungai Mulia 5 Malaysia is very much implemented. The focus of this research is (1). instilling multicultural values in Sanggar Bimbingan Mulia 5 Malaysia, (2). multicultural education methods at Sanggar Bimbingan Mulia 5 Malaysia (3). How to evaluate learning at the Sungai Mulia 5 Malaysia guidance studio In this research, researchers used qualitative research. Data was collected using three techniques, namely: (1). Interviews, (2) Observations, and (3) Documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. Data validity checking techniques use several things including: extending participation and triangulation. The results of this research are: (1) The students of Sanggar Guidance Sungai Mulia 5 Malaysia really appreciate even though they are of different races, likes, nationalities, even different countries, because they live in a multicultural environment, and can adapt to the surrounding environment, planting it by getting used to it every day. -day and accompanied by theory. (2) The children of Sanggar Guidance Sungai Mulia 5 Malaysia are educated with customs like in Indonesia from ceremonies, learning, customs, and when learning the language they also use Indonesian. (3) Evaluation of learning at Sanggar Guidance Sungai Mulia 5 Malaysia is the same as schools in Indonesia, there is an exam at the end of learning and daily tests